Unveiling paracrine dissemination and toxicity of neuronal TrkB-ICD via secretome signalling in Alzheimer’s disease - Coelho, Tiago Rodrigo da Costa (2021)
The brain-derived neurotrophic factor (BDNF) is a neurotrophin that binds to the TrkB full-length receptor (TrkB-FL), triggering cascades responsible for neuroprotection. This BDNF/TrkB-FL system is known to be impaired in Alzheimer’s disease (AD)due to an amyloid-β-mediated TrkB-FL cleavage, leading tothe formation of two fragments,a membrane-bound truncated receptor (TrkB-T’) and an intracellular domain fragment (TrkB-ICD). TrkB-ICD hastyrosine kinase activity, promotescognitive impairments,and modifiesgene expression.Notwithstanding, its intracellular clearance mechanisms remain elusive. Importantly, TrkB-ICD has been detected in cerebrospinal fluid of humans, questioning its release pathway. Interestingly, AD pathological features may be disseminated by extracellular vesicles (EVs) such as exosomes and microvesicles, which by incorporatingharmful mediators, candrive intercellular propagation of inflammatory, misfolded proteinsand toxic factors. Although AD remains as an untreated disorder, our lab designed a peptide, TAT-TrkB, capable of preventing TrkB-FL cleavage.As such,this project aimed at:i)exploreTrkB-ICD cellular clearance mechanisms;and ii)evaluate the efficacy ofTAT-TrkB in 5xFAD, an AD mouse model.Data withTrkB-ICD-expressingSH-SY5Y cells corroborated thatTrkB-ICD isa stable fragment with a half-life of approximately 6-8h. Studies evaluating the contributionof both the proteasome and autophagy pathways in TrkB-ICD clearance did not completely elucidate its degradation mechanisms,so far. We pioneeredthe discoveryof TrkB-ICD in microvesicles,and exosomesreleased by SH-SY5Y cells. This is a remarkable observation that may imply that TrkB-ICD can be disseminated among cells. propagatingits toxicity. The experiments performed to evaluate TAT-TrkB efficacyin the 5xFAD AD mouse modelwere done in the context of a pilot study and did not provide a coherent conclusion, prompting usto redesignthisin vivo study infuture work. Nevertheless, the obtained data strongly suggest that TAT-TrkB mayhave a beneficial role in learning and memory,asevaluated by the Morris Water Mazetest.